Counting the costs: understanding the extra costs of living with disability in Indonesia to advance inclusive policies within the SDG framework - Marlina, Irma; Wibowo, Ginanjar; Bastias, Desi Dwi; Sijapati Basnett, Bimbika; Prasetyo, Dinar Dwi; Nasiir, Mercoledi (Frontiers in Rehabilitation Sciences, 2024)
The Sustainable Development Goals (SDGs) serve as a valuable and multidimensional framework for monitoring progress on disability inclusion over time and among countries where reliable, disability disaggregated data is available. However, the SDGs alone do not provide insights into the causes of the social and economic disparities that people with disabilities face or offer specific policy solutions to alleviate them. This paper focuses on understanding the extra costs of living with disability in Indonesia to advance the country's commitment to further the rights of people with disabilities. It utilizes three primary estimation methods, combining an analyses of national survey data with primary data from interviews and focus group discussions. Findings reveal significant and varying costs based on disability type, severity and life cycle stages. It also highlights the unaffordability of these costs for most individuals with disabilities and their families. Leveraging these estimates, the paper proposes 'disability concessions' aligned with Indonesia's legal framework on disability inclusion, aiming to alleviate financial burdens through discounts across health, education, utilities and transportation. By contributing to methodological approaches in understanding extra costs of living with disability inclusion in emerging country context and promoting discussions on leveraging the results for disability inclusive policymaking, this paper supplements the SDG framework to foster disability inclusion.